Some issues of professional orientation of adolescents and adults with autism spectrum disorders - T.I. Morozova; B.V. Belyavskiy (Moscow State University of Psychology and Education, 2016)
For the last 3-4 years, the development of a comprehensive system of support for people with autism spectrum disorders in Russia has been accelerating. It is most evident in dealing with the issues of early assessment and intervention as well as elementary stage of education. However, the most problematic stage of autistic person's life begins after school age, around 18-21 years, and the general estimations of support effectiveness on the previous stages are mostly determined by the quality of life of an adult with autism spectrum disorder. An important aspect of such estimation is a professional activity - the most important factor of socio-economic wellbeing of an individual and their family, society and state. The authors' of the article have more than 30 years of experience in autism intervention, which show that the success of, for example, school education is largely defined by properly organized preschool support. All the same, the important factor of professional success of an adult with autism lies within the professional orientation, but despite the obvious importance of this process there is a distinct lack of research about it. The purpose of this work is to generalize the authors' experience and different experience in the field of professional orientation of adolescents and adults with autism spectrum disorders and to formulate some recommendations useful for practical work.